The effect of diet and host genotype on ceca microbiota of Japanese quail fed a cholesterol enriched diet - Liu, Shasha; Bennett, Darin C.; Tun, Hein M.; Kim, Ji-Eun; Cheng, Kimberly M.; Zhang, Hongfu; Leung, Frederick C. (Frontiers in Microbiology, 2015)
Two Japanese quail strains, respectively atherosclerosis-susceptible (SUS) and –resistant (RES), have been shown to be good models to study cholesterol metabolism and transportation associated with atherosclerosis. Our objective was to examine possible difference in cecal microbiota between these strains when fed a control diet and a cholesterol enriched diet, to determine how host genotype and diet could affect the cecal microbiome that may play a part in cholesterol metabolism. A factorial study with both strains and two diets (control, cholesterol) was carried out. Cecal content was collected from 12 week old quail that have been on their respective diets for 6 weeks. DNA was extracted from the samples and the variable region 3 to 5 of the bacterial 16S rRNA gene was amplified. The amplicon libraries were subjected to pyrosequencing. Principal Component Analysis (PCA) of β-diversity showed four distinct microbiota communities that can be assigned to the 4 treatment groups (RES/control, RES/cholesterol, SUS/control, SUS/cholesterol). At the Phylum level, the 4 treatment groups has distinct Firmicutes community characteristics but no significant difference in Bacteroidetes. Eubacterium dolichum was rare in RES/control but became overabundant in RES/cholesterol. An unclassified species of Lactobacillaceae was found in abundance in SUS/control but the same species was rare in RES/cholesterol. On the other hand, two Lactobacillus species were only found in RES/control and an unclassified Lachnospiraceae species was abundant in RES/cholesterol but rare in SUS/control. The abundance of 4 species of Lachnospiraceae, 3 species of Ruminococcaceae and one species of Coprobacillaceae was positively correlated with plasma Total Cholesterol, plasma LDL, and LDL/HDL ratio. Our study of cecal microbiota in these quail has demonstrated that selection for susceptibility/resistance to diet induced atherosclerosis has also affected the quail’s cecal environment to host distinctly different cecal microbiome.